A Dispositional Approach to Examine the Impact towards Students Stressors in Indian Context - Chandrasekar Therasa; Chidambaram Vijayabanu (LED Edizioni Universitarie, 2016)
The current study explored the relationship between big five personality factors and various stressors of the students who are undergraduate, postgraduate and research scholars from nine colleges in North Chennai. The study is based on quantitative data with descriptive research design. The 20-item personality inventory developed by Donnellen et al. (2006) was used to analyse their personality and the stressors was measured using MSSQ (Medical Student Stressor Questionnaire) scale developed by Yusoff (2011). A total of 250 students were selected as respondents using cluster random sampling technique. It revealed a significant positive relationship with neuroticism and three types of stressors (academic, inter and intra personal and social). It also throws light on the personality trait, namely openness to experience played a major role in predicting the academic performance (CGPA). Through regression, it can be concluded that personality has a significant positive relationship with both academic and social stressors. The findings will provide appropriate measures for educators by realizing the importance of personality the student possesses and applying suitable strategies for them to improve their academic performance. The dispersal of the study's findings will significantly help students and the educators in the region.